The Role of Perceived Social Support in Quality of Life Among Elderly People in North Bihar - kumar, Abhishek; Kumar, Dhrub (Journal of Neonatal Surgery, 2026)
Social relations are an important psychosocial resource in old age, especially when ageing is coupled with changes in family roles, social participation, health and mobility. In contrast, little empirical research exists on source-specific perceived social support and multidimensional quality of life (QoL) of the older persons in North Bihar, India. This study explored relationships between perceived family, friend and significant other support and all the physical, psychological, social, environmental and whole of life dimensions of quality of life of older people. A purposive sampling of 209 persons comprising 86 males and 123 females from various localities of North Bihar were selected for the studies. The Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure perceived social support and the WHOQOL-BREF was used to measure QoL. Descriptive statistics and Pearson product-moment correlations were used for data analysis. Overall perceived social support was found to have positive correlation with overall QoL (r = .378), psychological QoL (r = .332), environmental QoL (r = .313), social QoL (r = .244) and physical QoL (r = .207). Family support was significantly correlated with all domains of the QoL as well as overall QoL (r = .306). There was a strong source specific correlation with overall QoL with significant-other support (r = .363), family support and friend support (r = .290). Perceived social support is one of the key psychosocial factors associated with quality of life. The results suggest that family and non-family supportive relationships need to be integrated into community-based measures for enhancing well-being in older adults.